2015
DOI: 10.1017/s1742170515000307
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of the participation in agri-environment measures for organic farming

Abstract: Support for organic farming is a key strategy of rural development policies in several countries. This paper studied the\ud spatial pattern of participation in agro-environmnetal policy the policies designing to foster diffusion of organic farming.\ud The ultimate goal is to investigate the impact of local factors for improving the policy targeting. Indicators of spatial association and a spatial econometrics model were performed for the analysis. The results show regional agglomeration effects of the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Third, a growing number of studies focus on the spatial pattern of non-grain farmland (NGF) and find evidence for the spatial clustering of NGF [43][44][45]. Agglomeration economies may explain spatial clustering of NGF.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a growing number of studies focus on the spatial pattern of non-grain farmland (NGF) and find evidence for the spatial clustering of NGF [43][44][45]. Agglomeration economies may explain spatial clustering of NGF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schmidtner et al found evidence of economies of agglomeration in organic farming [47]. Boncinelli et al found that proximity reduces transaction and information costs [45]. Studies in China also showed that agglomeration of population, industries and technology affected on spatial pattern of farmland [48,49].…”
Section: Research Frameworkmentioning
confidence: 99%
“…The economics literature documents a strong linkage between the two pillars and which affects farmers' decision-making [41] and their territorial transitions [10,59] towards multifunctionality. In fact, both the first and second pillars maintain viable farming and agricultural profitability and can therefore contribute to investments in agriculture and to the adoption of environmentally friendly management systems.…”
Section: Discussionmentioning
confidence: 99%
“…Even after 20 years of application and a large share of expenditure allocated to AESs in national rural development budgets [2], evaluation reports and the scientific literature have determined that AESs have engendered lower-than-expected environmental impacts [3][4][5]. The economics literature points to poor targeting levels, low participation rates, the heterogeneity of compliance costs [6,7], the spatial distribution of participation, and the presence of information asymmetry between farmers and the government as the main reasons for unsatisfactory AES outcomes [8][9][10]. There have been a few recent attempts to investigate the relationship between the 'management option uptake' (i.e., the ways in which farmers access and participate in the scheme on a voluntary basis) and the ability of the scheme to deliver ecosystem services [11]; these studies conclude that the prescriptive nature of such programmes weakens the government's ability to promote effective environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on regional patterns of organic farming has focused on socio-economic and cultural factors, from policy support to agglomeration effects and from the philosophy of farmers to the development of markets for organic produce and organic seed [ 40,[51][52][53][54][55][56][57][58][59]. Whilst these factors are undoubtedly important, this study builds on evidence obtained at the landscape level on the role of environmental factors in shaping organic farming adoption [20,49] and suggests that biogeographic variables may play a contributing role in how widespread organic farming is becoming across entire countries.…”
Section: Discussionmentioning
confidence: 99%